Prenatal interventions to prevent bronchopulmonary dysplasia in animal models: a systematic review. (17th August 2016) - Jimenez, Julio; Richter, Jute; Toelen, Jaan; Deprest, Jan
Abstract: Objective: The objective of this study is to identify and systematically review in vivo animal studies on antenatal medical interventions to prevent bronchopulmonary dysplasia. Methods: An automated literature search was conducted using MEDLINE (Pubmed) and Embase including all studies using Medical Subject Headings (MeSH) and keywords following a step-by-step approach. All in vivo prenatal intervention studies in animal models mimicking key aspects of the pathophysiology of bronchopulmonary dysplasia were included. In view of relevance of the findings, an additional criterion was that outcomes at 48 h of life or beyond were available. The PRISMA statement concerning systemic reviews was applied and a quality checklist developed by the CAMARADES group was used. Results: In total, 518 abstracts were identified yet only eight studies were eligible for further analysis. Four studies involved administration of glucocorticoids, the other studies described therapy with epidermal growth factor, interleukin 1b, beta-naphthoflavone, or vitamin D. Outcomes were survival, pulmonary histology, lung function, and/or biochemical analysis. Conclusions: Though many in vivo experimental studies in animal models for bronchopulmonary dysplasia have been done, only few have looked into the effect of pre natal interventions and measured outcomes after at least 48 h of life. Most involve the use of antenatal glucocorticoids, although still only four.